Solve for y y/-5=-6

Math
y-5=-6
Multiply both sides of the equation by -5.
-5⋅y-5=-5⋅-6
Simplify both sides of the equation.
Tap for more steps…
Simplify -5⋅y-5.
Tap for more steps…
Cancel the common factor of 5.
Tap for more steps…
Factor 5 out of -5.
5(-1)⋅y-5=-5⋅-6
Factor 5 out of -5.
5⋅-1⋅y5⋅-1=-5⋅-6
Cancel the common factor.
5⋅-1⋅y5⋅-1=-5⋅-6
Rewrite the expression.
-1⋅y-1=-5⋅-6
-1⋅y-1=-5⋅-6
Simplify the expression.
Tap for more steps…
Move the negative one from the denominator of y-1.
-1⋅(-1⋅y)=-5⋅-6
Rewrite -1⋅y as -y.
-1⋅(-y)=-5⋅-6
-1⋅(-y)=-5⋅-6
Multiply -1(-y).
Tap for more steps…
Multiply -1 by -1.
1y=-5⋅-6
Multiply y by 1.
y=-5⋅-6
y=-5⋅-6
y=-5⋅-6
Multiply -5 by -6.
y=30
y=30
Solve for y y/-5=-6

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top